UGO1 Encodes an Outer Membrane Protein Required for Mitochondrial Fusion - Sesaki, Hiromi (The Rockefeller University Press, 2001)
Membrane fusion plays an important role in controlling the shape, number, and distribution of mitochondria. In the yeast Saccharomyces cerevisiae, the outer membrane protein Fzo1p has been shown to mediate mitochondrial fusion. Using a novel genetic screen, we have isolated new mutants defective in the fusion of their mitochondria. One of these mutants, ugo1, shows several similarities to fzo1 mutants. ugo1 cells contain numerous mitochondrial fragments instead of the few long, tubular organelles seen in wild-type cells. ugo1 mutants lose mitochondrial DNA (mtDNA). In zygotes formed by mating two ugo1 cells, mitochondria do not fuse and mix their matrix contents. Fragmentation of mitochondria and loss of mtDNA in ugo1 mutants are rescued by disrupting DNM1, a gene required for mitochondrial division. We find that UGO1 encodes a 58-kD protein located in the mitochondrial outer membrane. Ugo1p appears to contain a single transmembrane segment, with its NH(2) terminus facing the cytosol and its COOH terminus in the intermembrane space. Our results suggest that Ugo1p is a new outer membrane component of the mitochondrial fusion machinery.